PENYULUHAN SANITASI KOMUNAL DI DESA TAMBAK BARU KECAMATAN MARTAPURA KOTA KABUPATEN BANJAR - Eka Purnamasari; Akhmad Gazali; Robiatul Adawiyah (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2017)
Tambak Baru is one of 25 villages. Village located in the District Martapura Banjar district. The majority of the population are farmers Tambak Baru (peasant) and household handicraft industry and artisan labor. Geographically, the new Village Pond located at coordinates between 3.23594 ° S and 114 ° 35'30 "- 114.52134 ° East.Wastewater contained in Tambak Baru generally in the form of domestic waste / household. The waste water typically flows into the river nearby, so the burden of the rivers in the region is getting heavier and river water pollution level is high enough. It can be seen from the river in the region. And in the rainy season drainage is not functioning properly so frequent inundation at certain points.Based on the characteristics of the Tambak Baru, District Martapura Banjar Regency, it can be concluded that the aspect of social affecting people in Tambak Baru, District Martapura Banjar district in the act defecating carelessly, among other factors economic, education and mindset of the people in the act defecating , To achieve the target stop Babs performed triggered activity, in order to achieve behavioral change in behavior by simulation calculations Babs feces and fecal water, because people dump sludge into the river. The technical aspects of the constraints is the topography factor (nearby river with settlements), and lack of availability of land as a result of the density of homes that use a centralized waste management system and WWTP Communal.